Antiapoptotic Activity of Coxiella burnetii Effector Protein AnkG Is Controlled by p32-Dependent Trafficking - Eckart, Rita A. (American Society for Microbiology, 2014)
Intracellular bacterial pathogens frequently inhibit host cell apoptosis to ensure survival of their host, thereby allowing bacterial propagation. The obligate intracellular pathogen Coxiella burnetii displays antiapoptotic activity which depends on a functional type IV secretion system (T4SS). Accordingly, antiapoptotic T4SS effector proteins, like AnkG, have been identified. AnkG inhibits pathogen-induced apoptosis, possibly by binding to the host cell mitochondrial protein p32 (gC1qR). However, the molecular mechanism of AnkG activity remains unknown. Here, we demonstrate that ectopically expressed AnkG associates with mitochondria and traffics into the nucleus after apoptosis induction, although AnkG lacks a predicted nuclear localization signal. We identified the p32 interaction region in AnkG and constructed an AnkG mutant (AnkG(R22/23S)) unable to bind to p32. By using this mutant, we found that intracellular localization and trafficking of AnkG into the nucleus are dependent on binding to p32. Furthermore, we demonstrated that nuclear localization of AnkG but not binding to p32 is required for apoptosis inhibition. Thus, the antiapoptotic activity of AnkG is controlled by p32-mediated intracellular trafficking, which, in turn, seems to be regulated by host cell processes that sense stress.